Bogotà bag for pediatric Open Abdomen - Vito Briganti; Stefano Tursini; Caterina Gulia; Giovanni Ruggeri; Tommaso Gargano; Mario Lima (Journal of Pediatric Surgery Case Reports, 2020)
The management of a “Complex Abdomen” (CA) and the choice of the best way or technique to deal with it is still a challenge for surgeons. When there are the criteria to define an abdomen as a complex one, whether in emergency or elective surgery, the abdomen may need to remain open to allow access for re-operation and time for decompression. The use of an “Open Abdomen” (OA) as a surgical option permits an easy re-exploration, the control of the abdominal contents, the reduction of the risk of intra-abdominal hypertension (IAH) and consequent Abdominal Compartment Syndrome (ACS) and the preservation of the fascia for closure of the abdominal wall [1–4]. Many different techniques have been described to manage the OA and the Temporary Abdominal Closure (TAC) [5–7]. This kind of approach to the CA, well known by pediatric surgeons and widely used in the management of large gastroschisis, is now used also in other situations. We describe our experience with the Bogotà bag in one young man and three children affected by different pathologies, in the first and third one the OA was necessary because of a massive peritonitis due to acute appendicitis while in the last two cases a congenital digestive malformation was present at birth. The Bogotà bag technique is safe, easily managed and less expensive than other techniques and can be safely used in children and young adults.